Tanggung Jawab Pendidikan Menurut Alquran - Napitupulu, Dedi Sahputra (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2019)
Education is the most important factor in shaping human resources superior. In order to realize quality education so many factors that are responsible for and actively involved in advancing education. The following description is trying to explain the responsibilities of education based on the approach to librarianship and through analysis of the interpretation of the Qur'anic verses relating to responsibility for education. Specifically verses that will be examined is the surah Luqman/31:12-19 and Surah at-Tahrim/66:6. The results of the analysis of the research indicates that real education responsibilities given to four groups, namely: 1) parents as the first educators, 2) Educators/teachers that provide formal science at educational institutions, 3) Learners as people who need guidance, and 4 facilitate the sustainability of the Government) of education